PP.27.13: PREVALENCE OF VASCULAR DAMAGE IN HYPERTENSIVE PATIENTS ACCORDING TO BLOOD PRESSURE CONTROL. (June 2015) - Salvetti, M.; Paini, A.; Agabiti-Rosei, C.; Bertacchini, F.; Maruelli, G.; Colonetti, E.; Donini, C.; Germano, R.; Casella, E.; Agabiti-Rosei, E.; Muiesan, M.
Abstract : Objective: Current hypertension guidelines recommend evaluation of preclinical organ damage (OD) for cardiovascular risk assessment. Prevention and/or regression of OD is one of the main goals of antihypertensive treatment. To assess the differences of vascular OD in a large group of hypertensive patients (HT) and normotensive subjects (N) patients according to antihypertensive treatment and blood pressure (BP) control (BP < 140/90 mmHg). Design and method: A total of 319 subjects (mean age 54 ± 7 yrs), 49 % males, 61 % hypertensives (55 % treated), underwent clinical examination with BP measurement (clinic and 24 hours) and standard laboratory examinations. We compared carotido-femoral pulse wave velocity (PWV), ultrasound carotid intima media thickness (IMT) and wall to lumen ratio of retinal arterioles (WLR) among normotensive subjects (N, n = 125), 87 untreated patients with essential hypertension (UHT), 66 treated patients with controlled essential hypertension (TC_HT) and 41 treated patients with uncontrolled essential hypertension (TUC_HT). OD was defined, according to ESH ESC 2013 Guidelines. Results: In TUC_HT a significant increase in retinal WLR (0.33 + 0.19 and 0.23 + 0.13, p = 0.013) and in carotid mean-max IMT (1.62 + 2.9 vs 0.98 + 0.16, p = 0.014) was observed, as compared to normotensive subjects, while no significant differences between TC_HT and NT were demonstrated. In normotensives cfPWV was significantly lower as compared to TUC_HT (p < 0.05), but not as compared to TC_HT. Conclusions: In hypertensive patients, WLR, IMT and aortic stiffness are slightly, but not significantly, increased when blood pressure is controlled. Vascular damage in treated uncontrolled hypertensives might represent the consequence of increased BP, but might also contribute to poor BP control.